Changing intergovernmental fiscal relationship: impact of the 1986 Tax Reform Act on state and local governments - Watson, Douglas J.; Vociono, Thomas
This article briefly examines the historic role of federal financial support to state and local governments both through budget expenditures and tax policies. Next, specific provisions in the Tax Reform Act of 1986 and their impacts on state and local governments are examined. The primary focus is one of the most important areas of impact - tax exempt bonds. Lastly, this article explores the argument that these tax law changes have significantly altered the balance of power between the federal government and the states and localities within the federal system
Keywords: Tax Reform Act,1986; Federal Aid